Your dilemma, my identity: Unusual immunogenetic profiles of pediatric B cell acute lymphoblastic leukemia - Anurag Gupta; Manu Goyal; Koteswara Rao Nidamanuri; Palanki Satya Dattatreya (Indian Journal of Pathology and Microbiology, 2014)
B-cell acute lymphoblastic leukemia (B-ALL) is characterized by CD19 expression, which is one of the most important prerequisites, along with expression of CD10, CD22 and/or CD79a. Rearrangements involving MLL gene are seen in CD10− B-ALL (pro-B cell origin) and t(9;11)(p21;q23) is most commonly reported in acute myeloid leukemia (AML), where it is known to carry very good prognosis in pediatric AMLs and rarely in acute lymphoblastic leukemia (ALL). We report a case of CD10 + , CD19− pediatric ALL with rearrangements of MLL gene as a result of t(9;11)(p21;q23), thus conferring a very poor prognosis. The case emphasizes use of comprehensive panel of antibodies for flow cytometric immunophenotyping and cytogenetic correlation for correct diagnosis and prognostication.